ISSUES OF PRODUCTION DEVELOPMENT IN INDUSTRIAL ENTERPRISES - Akbarovich, Yadgarov Akram (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
In the article, the volume of industrial products produced by industrial enterprises to meet the growing needs of the population from year to year, as well as ensuring the employment of the country's population as a necessity for the development of production enterprises in industrial development, is analytically studied on the basis of statistical indicators. As a result of improving the production of industrial products, as well as ensuring the domestic market, the issues of priority development of industrial development by directing industrial products to export have been studied, suggestions and recommendations have been made